The practical aspects of local development of entrepreneurship and innovation in travel companies - Ewa Kulińska; Monika Odlanicka-Poczobutt (Foundations of Management, 2017)
The aim of this publication is to present the effects of one of the projects conducted in Opole Province, titled 'The effective transfer of knowledge from science to industry in Opole Province' and its impact on the practical aspects of the local development of entrepreneurship and innovation in travel companies. The presented material constitutes an attempt to answer the research problems associated with the introduced innovations. These problems have been formulated as the following questions: Is the GPS functional enough to significantly improve transportation services? Does the cost of implementing the system not exceed the profits it generates? Does the use of GPS in performing transportation services cost-effective also for small businesses? Is a company that uses the GPS able to meet the increasing customer expectations? How can a business benefit as a result of implementing the system? To verify this objective, theoretical research tools were used, such as: analysis, synthesis, generalizations, and comparisons. In terms of practical methods, the following found application: observation method (gathering information on companies, interviews with employees, analysis of documents) and analytical method.
Keywords: 650; development of entrepreneurship business development; innovations; research projects; Oslo Manual; tourism